The SGLT2 inhibitor empagliflozin does not stimulate compensatory appetite responses in patients with excess adiposity and type 2 diabetes [Abstract] - Melanie Davies; Emma Baldry; Danielle Bodicoat; Sudesna Chatterjee; Charlotte Edwardson; Laura Gray; Kamlesh Khunti; Jack Sargeant; David Stensel; David Webb; John Wilding; Scott Willis; et al. (2020)
No description supplied